2019
DOI: 10.3390/su11195444
|View full text |Cite
|
Sign up to set email alerts
|

Fish Communities, Habitat Use, and Human Pressures in the Upper Volta Basin, Burkina Faso, West Africa

Abstract: Human pressures and loss of natural fish habitats led to a decline in fish populations in terms of abundances, biodiversity, and average size in sub-Sahelian Burkina Faso. Little knowledge exists about fish assemblages regarding their composition, their habitat preferences, or their sensitivity to or tolerance of human pressures. This research provides the first data-driven basis for sustainably managing fish and associated aquatic and terrestrial habitats. Surveys in four different regions sampled 18,000 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
4
6
0
Order By: Relevance
“…Other studies have underlined the importance of physical-chemical variables for biomonitoring in tropical streams (Thorne and Williams, 1997;Lakew and Moog, 2015). Indeed, authors have demonstrated that the intense land use in riparian zone can deteriorate the quality of water physical and chemical variables (Kaboré et al, 2018;Meulenbroek et al, 2019). In this study, the values of the main physicochemical variables are similar to those obtained by Kaboré et al (2018) in the reference sites of Burkina Faso.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Other studies have underlined the importance of physical-chemical variables for biomonitoring in tropical streams (Thorne and Williams, 1997;Lakew and Moog, 2015). Indeed, authors have demonstrated that the intense land use in riparian zone can deteriorate the quality of water physical and chemical variables (Kaboré et al, 2018;Meulenbroek et al, 2019). In this study, the values of the main physicochemical variables are similar to those obtained by Kaboré et al (2018) in the reference sites of Burkina Faso.…”
Section: Discussionsupporting
confidence: 78%
“…Here we found also a strong and negative correlation between the electrical conductivity and EOTtaxa. Indeed, the high conductivity is often an indicator of water pollution because it is likely to be affected by different riparian land use types (DeTroyer et al, 2016;Kaboré et al, 2016aKaboré et al, , c, 2018Meulenbroek et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Deforestation, habitat degradation, and overfishing were identified as major threats to natural fish population in sub-Saharan Africa and the same applies to Ethiopia (e.g. [ 23 , 37 , 66 ]). Pollution and lake level changes will exacerbate the reduction of populations sizes and thus speed genetic drift effect further reducing genetic diversity of fish populations [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In situ parameters such as, pH, electrical conductivity (Cond), temperature, and dissolved oxygen (Oxy) were measured with field multimeters (WTW 340i) before fish and macroinvertebrate sampling. Fish communities were sampled in Koubri (05 sites) and Nazinga (06 sites) using two types of equipment including electric fishing and cast net, and the habitats type were noted following sampling approach described by (Meulenbroek et al, 2019). For electric fishing, the backpack-generator ELT60-IIH from Hans Grassl was applied.…”
Section: Data Collectionmentioning
confidence: 99%